5D superresolution imaging for a live cell nucleus. (April 2021) - Chu, Li-An; Chang, Shu-Wei; Tang, Wei-Chun; Tseng, Yu-Ting; Chen, Peilin; Chen, Bi-Chang
Abstract : With a spatial resolution breaking the diffraction limit of light, superresolution imaging allows the visualization of detailed structures of organelles such as mitochondria, cytoskeleton, nucleus, and so on. With multi-dimensional imaging (x, y, z, t, λ), namely, multi-color 3D live imaging enables us fully understand the function of the cell. It is necessary to analyze structural changes or molecular interactions across a large volume in 3D with different labelled targets. To achieve this goal, scientists recently have expanded the original 2D superresolution microscopic tools into 3D imaging techniques. In this review, we will discuss recent development in superresolution microscopy for live imaging with minimal phototoxicity. We will focus our discussion on the cell nucleus where the genetic materials are stored and processed. Machine learning algorism will be introduced to improve the axial resolution of superresolution imaging.